Towards inclusive development through harnessing demographic dividend? Empirics for Africa - Mesfin Mulugeta Woldegiorgis (Journal of Social and Economic Development, 2023)
Africa is now at a historical moment of swift demographic transition, which has the potential to harness the demographic dividend and foster inclusive development. However, just like the abundant natural resources, the growing population can be either a blessing or a curse. For instance, the economic growth and swift demographic transition in the last two decades have been tripled by a drastic political movement led by the protruded youth cohort. This paper, therefore, explores an empirical elucidation for the paradox and its remedy. It presents the drivers and time span of the potential demographic dividend for selected African countries. The panel data regression encompasses 34 African countries. However, the time span of the first demographic dividend is revealed for 47 African countries. The ordinary least square regression for the clustered dataset shows that harnessing the demographic dividend requires investment in family planning, gender parity, digitalization, industrialization, and job creation. The unique contribution of the paper is that it extends the demographic dividend discourse into the emerging inclusive development approach and presents pertinent empirics.
Keywords: 300; Surplus labour; Remittance; Demographic bomb; Inclusive institutions